Предмет: Алгебра,
автор: kchistyakowa
Решите уравнение: (3x−5)/3=(x−4)/2.
Ответы
Автор ответа:
0
(3x−5)/3=(x−4)/2.
2 (3x−5) = 3 (x−4)
6x -10 = 3x -12
3x = -2
x = -2/3
2 (3x−5) = 3 (x−4)
6x -10 = 3x -12
3x = -2
x = -2/3
Автор ответа:
0
(3x−5)/3=(x−4)/2
(3х-5) *2 = (х-4)*3
6х -10 = 3х -12
6х- 3х = -12 +10
3х = -2
х = - 2/3
(3х-5) *2 = (х-4)*3
6х -10 = 3х -12
6х- 3х = -12 +10
3х = -2
х = - 2/3
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Информатика,
автор: KaBo228ban
Предмет: История,
автор: eldomioq
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: dDaniill